An objective and reliable electrophysiological marker for implicit trustworthiness perception. Issue 3 (9th April 2020) - Swe, Derek C; Palermo, Romina; Gwinn, O Scott; Rhodes, Gillian; Neumann, Markus; Payart, Shanèle; Sutherland, Clare A M
Abstract: Trustworthiness is assumed to be processed implicitly from faces, despite the fact that the overwhelming majority of research has only involved explicit trustworthiness judgements. To answer the question whether or not trustworthiness processing can be implicit, we apply an electroencephalography fast periodic visual stimulation (FPVS) paradigm, where electrophysiological cortical activity is triggered in synchrony with facial trustworthiness cues, without explicit judgements. Face images were presented at 6 Hz, with facial trustworthiness varying at 1 Hz. Significant responses at 1 Hz were observed, indicating that differences in the trustworthiness of the faces were reflected in the neural signature. These responses were significantly reduced for inverted faces, suggesting that the results are associated with higher order face processing. The neural responses were reliable, and correlated with explicit trustworthiness judgements, suggesting that the technique is capable of picking up on stable individual differences in trustworthiness processing. By demonstrating neural activity associated with implicit trustworthiness judgements, our results contribute to resolving a key theoretical debate. Moreover, our data show that FPVS is a valuable tool to examine face processing at the individual level, with potential application in pre-verbal and clinical populations who struggle with verbalization, understanding or memory.